ANALYSIS OF HEAT TRANSFER TO A SHEET-TYPE HEAT EXCHANGER PLACED IN RUNNING WATER-THERMAL ENERGY EXTRACTION FROM IRRIGATION WATER (14th CONSTRUCTAL LAW CONFERENCE | 10-11 October 2024, Bucharest, Romania, 2024)
A sheet-type heat exchanger has been extensively used as a device for extracting heat from the ground soil. This heat exchanger consists of polyethylene capillary tubes bundled together in a sheet, positioned between two header pipes that serve as the inlet and outlet for circulating brine. The bundled thin tubes, with an outer diameter of 6 mm and an inner diameter of 5mm, are highly flexible, allowing for easy winding and bending. This flexibility provides significant freedom in configuring the device within the soil. This paper examines the possibility of using the same heat exchanger to collect heat from water flowing in irrigation channels and rivers. We discuss an analytical method capable of predicting the performance of the heat exchanger when it is positioned parallel to the water flow. In this analysis, we employ the concept of overall heat transfer coefficient to evaluate a single polyethylene tube. Specifically, we determine the dimensionless inner convective heat transfer coefficient, known as the inner Nusselt number, for laminar flow conditions. Meanwhile, the outer convection heat transfer coefficient is derived from forced convection correlation obtained from an isothermal flat plate. Additionally, numerical simulations are conducted to account for the influence of header pipes on the flow field and to relax the assumption of a constant outer wall temperature. We find that the analytical and numerical results generally agree. Furthermore, we compare the analytically predicted results with available experimental data, revealing agreement between the predicted and experimentally obtained heat transfer rates.
Keywords: Heat transfer; Convection; Heat exchanger; Irrigation water; Energy tapping; Agricultural use